1992
DOI: 10.1159/000126149
|View full text |Cite
|
Sign up to set email alerts
|

DOPA Accumulates in the Hypothalamic-Hypophysial Portal Vessels and Is Taken into the Anterior Pituitary of NSD-1015-Treated Rodents

Abstract: DOPA was measured in the anterior pituitary and hypothalamic-hypophysial portal blood after treatment with NSD-1015, a DOPA decarboxylase inhibitor. NSD-1015 caused DOPA to accumulate in the anterior pituitary of mice and rats, and increased DOPA in the hypothalamic-hypophysial portal blood of rat. Serum prolactin was also increased. Interruption of the anterior pituitary blood supply from the hypothalamic-hypophysial system by cannulation of the entire pituitary stalk eliminated the NSD-1015-induced DOPA accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In our study, the concentrations of L-Dopa tested in the experiments were 1 and 10 µM. These selected concentrations are comparable to the levels found in the plasma of portal vessels (12). To elucidate whether L-Dopa treatment alters the secretion of ACTH, we examined the effects of locally produced DA and AADC inhibition on basal and CRH-stimulated secretion of ACTH.…”
Section: Accepted Articlementioning
confidence: 98%
See 3 more Smart Citations
“…In our study, the concentrations of L-Dopa tested in the experiments were 1 and 10 µM. These selected concentrations are comparable to the levels found in the plasma of portal vessels (12). To elucidate whether L-Dopa treatment alters the secretion of ACTH, we examined the effects of locally produced DA and AADC inhibition on basal and CRH-stimulated secretion of ACTH.…”
Section: Accepted Articlementioning
confidence: 98%
“…In fact, Telford et al have shown that the concentration of L-Dopa is higher in portal blood than in peripheral circulation. The authors conclude that the major source of L-Dopa in the anterior pituitary is the portal blood supply because L-Dopa was not detected in this lobe when the portal circulation was interrupted by separating the pituitary stalk (12). Based on reported concentrations in portal blood of DA (6 ng/ml in diestrus rats; (11)) and L-Dopa (40 ng/ml in female rats treated with NSD 1015; (12)), we could assume that the greatest contribution of DA would be from an endogenous (anterior pituitary) source.…”
Section: Accepted Articlementioning
confidence: 99%
See 2 more Smart Citations